Analisis Kualitas Website Terhadap Kesuksesan Penggunaan E-Learning Dengan Menggunakan Model Measuring E-learning Sistems Success (MELSS) - Wahyu Widodo (JUMANJI (Jurnal Masyarakat Informatika Unjani), 2020)
The e-learning system is created to optimize the teaching and learning process for lecturers and students so that they can interact online without limitation of time and space. Youth facilities provided by e-learning such as uploading lecture material, assigning assignments, giving quizzes, announcing all information related to lectures to providing scores on the results of assignments given to students can be carried out. However, based on statistical data on access to the e-learning system, less than 50% of the interest of lecturers to use e-learning facilities is still not optimal. The use of the system is not optimal due to user dissatisfaction, the impact has an effect on system user loyalty. In this study will examine the Measuring E-Learning Systems Success Model (MELSS) with 4 variables related to the quality of the website and 6 variables related to user perceptions. Variables related to website quality: technical quality of the system, quality of content and information, quality of learning systems, quality of service. While the 6 variables related to user perceptions include: user satisfaction, intention to use, system users, system loyalty, benefits to use, and achievement of goals. The research sample that will be used is teaching staff, and students who use e-learning using purposive random sampling technique. The results of the hypothesis in this study there are 7 empirical evidence of factors that influence the successful use of e-learning.